Contrastive Study Of Proverbs With A Hydronym Component In English And Uzbek Languages (The Peerian Journal, 2025)
This article explores the contrastive analysis of proverbs containing hydronym components in English and Uzbek languages. Proverbs, as a part of the linguistic and cultural heritage of nations, reflect people's perceptions of water bodies and their significance. The study examines similarities and differences in meaning, usage, and cultural representation of hydronymic proverbs in both languages